Stock Valuation And Business Performance Of Property Industry Post Covid-19 Era (Case Study Of Pt Bumi Serpong Damai Tbk) - William Theodorus Wijaya william (Al-Makki Publisher, 2023)
In 2019 the pandemic Covid-19 caused sharp decline on Indonesian economy, yet in 2021 the economic condition started to recover, indicated by 7% increase in Gross Domestic Product and Consumer Confidence Index. One sector influenced by strong economic recovery is property industry, furthermore government gave stimulus to boost property industry growth. PT Bumi Serpong Damai Tbk (BSDE) is a leading property developer having various projects and land bank across Indonesia. Post Covid-19 era, the financial performance of PT Bumi Serpong Damai Tbk showed a good condition, the evidence is the increase in company profitability and decline in the debt. The fundamentals contrast with the stock price as the price declined even in the recovery phase. This condition encourages the writer to do the research on PT Bumi Serpong Damai Tbk stock valuation and whether the share is classified as overvalued or undervalued. The research will utilize secondary such as financial reports, annual reports, public expose from idx.co.id, tradingview, and other literature sources. The methodology to process the data is Discounted Cash Flow valuation method to find the actual intrinsic value and value-added intrinsic value, to find the fair value using Net Asset Value valuation method. The added value is a proposal to developing housing projects for Generation Z with goal to increase the company share price. The actual intrinsic value is IDR 1,250 per share with 6.40% margin of safety and the added-value valuation method is IDR 1,612 per share with 37.82% margin of safety. The result of Net Asset Value method is fair value of IDR 2,554 per share and 118.29% margin of safety. Finally, the author will determine if the stock of PT Bumi Serpong Damai Tbk is undervalued or overvalued and give investment recommendations.